Functional morphology of the metapleural gland in workers of the ant crematogaster inflata (hymenoptera, formicidae) - Hashim, Rosli; Ito, F.; Billen, J. (2011)
Workers of Crematogaster inflata possess the largest metapleural glands (relative to body size) known among ants, with reservoirs extending anteriorly up to the junction between the pro-and the mesothorax, and with over 1400 secretory cells on both sides together. This large secretory capacity is related to the gland's defensive function, which, in members of this species, is directed against larger arthropod and vertebrate enemies, and apparently not against microorganisms, in contrast to other ants, where the gland produces antibiotics. The gland is not equipped with any direct musculature. Secretion release is probably caused by contraction of the oblique longitudinal thorax muscles or by passive expulsion caused by external pressure.